Family Factor as an Impediment to Effective Mental Health Service Utilization Among Behavioral Patients in Benin City, Edo State, Nigeria - Omorogiuwa, Trace B.E.; Odore, Sulyman A. (NIU Journal of Social Sciences; Vol 11 No 3 (2025): NIU Journal of Social Sciences, Vol. 11 No. 3, September 2025, 2025)
This study aimed to explore family factors as impediments to effective mental health service utilization among behavioural patients in Benin City. Specifically, it examined how family beliefs and financial capability influence mental health services utilization. A qualitative narrative research design was employed, involving in-depth interviews with 14 informants which comprised 8 mental health outpatients and 6 mental health professionals from the Federal Neuropsychiatric Hospital, Uselu. The collected data were analysed thematically using Braun and Clarke’s method. Findings revealed that family beliefs, particularly cultural and spiritual interpretations of mental illness, significantly hinder timely access to psychiatric care and leading to a preference for traditional and religious interventions over medical treatment. Additionally, financial incapacity emerged as a major barrier, with patients and mental health professionals reported that the cost of medications, consultations, and transportation discouraged sustained treatment and led to relapses. This study therefore concluded that both belief and economic hardship within families are major obstacles to mental health service utilization in Benin City as these factors delay diagnosis, interrupt treatment and ultimately worsen patient outcomes. Given the conclusion, it is recommended that culturally sensitive mental health education campaigns be implemented to dispel myths and promote biomedical care and advocates for government-subsidized mental health services and social welfare support for low-income families to reduce financial burden and improve treatment adherence. Keywords: Family, Mental Health, Mental Health Disorder, Mental Health Service Utilization, Behavioural Patients, Belief, Financial Capability.